“Para além do aquário: O bildungsroman feminino em Lígia Fagundes Telles” - GOMES, Lízia Adriane Freire Ferreira (2023)
Bildungsroman emerged as a subgenre of the novel that had recognition in nineteenth century in Germany and influenced the production of works around the world over time. Thus, this genre is identified as a narrative in which the formation of the subject prevails, pointing out the phases of growth, development and maturation. Since its inception, the Bildungsroman has undergone revisions in Western literature, among them the possibility of a female-trained gender, which was once a strictly masculine field. Regarding to Brazil, the Brazilian writer Lygia Fagundes Telles produced short stories and novels, contributing to the modernist movement of the third generation of the twentieth century, focusing on female characters and their internal dilemmas. In the 60s, in particular, her literary expression showed a female subject in tune with the sociopolitical environment, noting the presence of the role of women in transformation and her frank psychological and social growth. It is in this logic that this present dissertation intends to analyze one of her works, Summer in the aquarium (1964), whose plot and its characteristics clearly point to the process of growth and maturation of the female character Raíza, demonstrating that it aligns with the characteristics of the traditional Bildungsroman, making a revision of the genre and can be classified as a novel of female formation. Thus, the present work intends to highlight this composition, which involves the constitution of the characters, especially the protagonist, as well as the specificities of this modern narrative genre, in the female perspective. In order to prove this proposal, it is intended to address the canon and the studies on Bildung, which began in Germany, up to the manifestations that expanded space for the insurgency of the gender of female formation in the world and in Brazil, in order to highlight the characteristics of this and observe them in the production of Lygia, in Summer in the aquarium. As for the methodology, the research is qualitative, bibliographic and interpretive, through the historical synthesis of the genre, going through the changes that occurred in its formal and contentist structure, as well as the observation and analysis of micro and macro characteristics of the work, demonstrating the existence of a narrative of female formation in the Lygian work in question. As far as the theoretical contribution is concerned, there is the approach of studies on traditional Bildungsroman, developed by Wilma Patrícia Maas (1999) and Franco Moretti (2020), and on the possibility of a novel of female formation, the national work of Cristina Ferreira Pinto (1990) will be highlighted. Such theoretical legitimations allow the realization of the study on the gender of female formation in Telles, besides helping in the understanding that this subgenre contributes to the expression and singularity of the literary richness in the female modernist national novel.